Analisis Perbandingan Performansi Server VoIP pada Komputer Papan Tunggal dan CPU Konvensional - Anselmus Xavereyno (Politeknik Negeri Malang, 2018)
This journal will briefly explain the comparison of voice over internet protocol server performance on two types of computers, namely single board computer or single board cirucuti (SBC) and conventional CPU. More specifically, it is on three server bases, namelyRaspberry Pi 3, Raspberry Pi 2 and conventional CPU. The background for taking the topic of this thesis is the development of SBC which is claimed to be able to go beyond conventional CPU. Although the specifications and age are able to compensate for or even exceed conventional CPUs, further research is needed in the form of performance comparisons. The performance comparison referred to includes the number of extensions that can be stored, simultaneous calls that can be served, usage of processor capacity, and usage of memory capacity. Tests carried out on the intranet network of State Polytechnic of Malang. The results of the test show that the three servers are able to store at least 100 extensions, can accommodate 60 online clients at the same time, can accommodate at least 30 simultaneous calls. The average use of the processor capacity by the Raspberry Pi 3 is 32%, the Raspberry Pi 2 is 43%, while the conventional CPU is 69%. The average RAM usage by the Raspberry Pi 3 is 296.96 MB, the Raspberry Pi 2 is 215.04 MB, and by the conventional CPU is 365.52 MB.